Prediction of Peak Aerobic Power among Costa Rican Older Adults - Peralta Brenes, Mariana (2018)
Introduction: The peak oxygen uptake (VO2peak) is considered a valid indicator of the cardiovascular system function, and when measured on a metabolic cart it is considered the gold standard for cardiorespiratory fitness. Prediction equations have been developed to indirectly determine VO2 peak; however, there are no equations specific to Costa Rican older adults. Aim: To develop a VO2peak prediction equation for Costa Rican adults over 60 years using the distance achieved on the Six minutes Walking Test (6MWT) and anthropometrical measures. Materials and Methods: Seventy-nine adults (Mean age=68.8±4.79 yr.) read and signed the informed consent, then scanned on DXA for body composition, then measured the HR before and after the 6MWT. Following a 10-minutes recovery period from the 6MWT, they performed a VO2peak treadmill test with breath-to-breath calorimetry gas analysis. The prediction model included body weight, height, Body Mass Index (BMI), body fat mass index, distance on the 6MWT, and change in Heart Rate (HR) following the 6MWT. Results: The prediction equation was VO2peak=17.59+0.028 {6MWT(m)}–0.256{BMI (kg/m2)}–2.567 (gender: 0 male, 1 female)±3.25 ml•kg-1•min-1 (R2 =0.48). A strong correlation (r=0.70, p<0.01) between predicted and measured calorimetry VO2peak values was obtained; yet, a poor concordance based on Lin’s coefficient (r=0.61). Conclusion: A VO2peak prediction equation with high accuracy and highly correlated to directly-measured VO2peak was developed for urban Costa Rican older adults. Non-specific population equations are not valid to predict VO2peak in urban Costa Rican older adults.